2011
DOI: 10.1007/s00268-011-1126-3
|View full text |Cite
|
Sign up to set email alerts
|

Relative Adrenal Insufficiency in the Critical Care Setting: Debunking the Classic Myth

Abstract: Hyponatremia, hyperkalemia, hypercalcemia, and hypoglycemia do not predominate in RAI and laboratory values are of minimal value in predicting patients with RAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In a series of 108 patients with idiopathic adrenal insufficiency, only 6 (5.5%) patients were complicated by mild hypercalcemia (9). In a recent study, although 112 (53%) of the 212 ICU patients were diagnosed as having latent adrenal insufficiency, no patients developed overt hypercalcemia (10). In this study, we found the prevalence of hypercalcemia due to adrenal insufficiency to be 1.3% in HD patients at a tertiary hospital.…”
Section: Discussionmentioning
confidence: 44%
“…In a series of 108 patients with idiopathic adrenal insufficiency, only 6 (5.5%) patients were complicated by mild hypercalcemia (9). In a recent study, although 112 (53%) of the 212 ICU patients were diagnosed as having latent adrenal insufficiency, no patients developed overt hypercalcemia (10). In this study, we found the prevalence of hypercalcemia due to adrenal insufficiency to be 1.3% in HD patients at a tertiary hospital.…”
Section: Discussionmentioning
confidence: 44%
“…Hypercalcemia in adrenal insufficiency is usually mild to moderate [ 4 - 5 ]. In a recent study, 53% of 212 intensive care unit patients were diagnosed with latent adrenal insufficiency, but none of these patients developed overt hypercalcemia [ 6 ]. The unusual feature of this case was the severe hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids lead to eosinopenic effects by stimulating eosinophil apoptosis. The presence of eosinophilia in critically ill patients is associated with clinical signs of adrenal insufficiency (5). All albumin levels were >2.5 mg/dL.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This condition is called critical illness-related corticosteroid insufficiency or relative adrenal insufficiency (RAI) (4). Clinically apparent adrenal insufficiency is usually rare in critically ill patients (5). Adrenal function is usually assessed by measuring the serum concentrations of total cortisol, free cortisol, or salivary cortisol levels (6).…”
Section: Introductionmentioning
confidence: 99%